PELATIHAN PEMBUATAN ABON IKAN TUNA DIKELURAHAN LAPPA KECAMATAN SINJAI UTARA KABUPATEN SINJAI - Asdinar Wahid Awaluddin; Benget Hutagaol; Wahyono; Fritz Mangundap; Nurfata Andriani; Kurniawati (Fakultas Ekonomi dan Bisnis, 2023)
This community service was carried out in Lappa Village, North Sinjai District, Sinjai Regency. The purpose of this PKM is to empower the community, especially the wives of Fishermen in Lappa Village to increase knowledge and skills in processing fish with the basic ingredients of tuna fish into economically valuable processed food products, so as to improve the economy of the Lappa Village community, especially increasing the family income of fishing communities. In Lappa Village there is a large and crowded fish auction site. TPI Lappa is the center of fish landing in Sinjai Regency. The targets or partners are the Rubon's tuna shredded MSME Group and Lappa Village Fisherwomen, totaling 20 people. The results of this activity were that the training participants were able to make shredded tuna fish.